Interpolation in Thucydides - Maurer, Karl. (Mnemosyne, Supplements, 1995)
The scraps of hard evidence are carefully sifted from the putative so as to uncover the probable extent and nature of interpolation in Thucydides. This gives a coarse but firm "typology," which may be of some use in the study of other MS traditions, and clarifies hard passages many of which are discussed in depth, so that the book's Index Locorum can be a tool for students of this author. Separate chapters examine evidence given by MS disagreement, by a long inscription, by papyri, by scholiasts, by Valla's translation and more. A chapter analyzes the types of mechanical "interpolation" another, the hypothesis of Hellenistic "editing." Constant close attention is paid to the stemma codicum (discussed also in an appendix) and to the smallest idiosyncrasies of Thucydides' style.